2022
DOI: 10.1017/s1368980022002415
|View full text |Cite
|
Sign up to set email alerts
|

Senior food insecurity in the USA: a systematic literature review

Abstract: Objective: Understanding the factors associated with senior food insecurity is key to understanding senior-specific needs to develop targeted interventions and ultimately lower the prevalence and the incidence of food insecurity. We aimed to systematically review published literature and summarize the associated factors of food insecurity in older adults in the US. Design: We searched Pubmed, Scopus, Web of science, EconLit, and JSTOR databases for peer-reviewed articles published in Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Several studies found similar results. For example, Mavegam Tango Assoumou et al (2023) found that among older adults, food-insecure respondents tended to be younger. Berning et al (2022) found that older households are more food secure than younger households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found similar results. For example, Mavegam Tango Assoumou et al (2023) found that among older adults, food-insecure respondents tended to be younger. Berning et al (2022) found that older households are more food secure than younger households.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic factors are similarly linked to food insecurity. For example, Facchini et al (2014) and Mavegam Tango Assoumou et al (2023) report that low maternal education, family income, and receipt of income assistance positively correlated with food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that food insecurity is prevalent among older adults and pregnant women in high‐income countries and is associated with numerous correlates such as lower income, poor health outcomes, and limitations in physical functioning. Targeted interventions, including food and nutrition safety nets and medication assistance programs, are warranted to address these issues 30,31 …”
Section: Relevance Of the One Health Approach For Clinical Practice A...mentioning
confidence: 99%
“…Targeted interventions, including food and nutrition safety nets and medication assistance programs, are warranted to address these issues. 30,31 In 2017, areas with the highest prevalence of food insecurity included Sub-Saharan Africa, Latin America, and the Caribbean; the lowest rates of food insecurity were observed in North America, Europe, and Central Asia. Risk factors for experiencing food insecurity include low levels of education, weak social networks, and the lack of support from friends and family in times of need.…”
Section: Food Insecuritymentioning
confidence: 99%
“…This was intensified amidst the COVID-19 pandemic, with worldwide food shortages, increased food prices and loss of income making food insecurity more visible (3). Part of the research on food insecurity has focused on target populations that appear to be at risk for food insecurity, such as low-income households, ethnic minorities and senior citizens (4)(5)(6)(7)(8)(9). In the Netherlands, limited food security research has been done, but it has identified a 73% prevalence of food insecurity among food bank recipients and a 26% prevalence in disadvantaged neighborhoods (10,11).…”
Section: Introductionmentioning
confidence: 99%